Segmental reporting by Malaysian companies : IAS 14 versus MASB 22. - Ismail, Hashanah; Yusof, Nurul Adillah (David Publishing, 2009)
This paper reports on the effects of a local standard, MASB 22, on disclosure practices among Malaysian companies and whether the introduction of MASB 22 has resulted in greater level of disclosure with respect to segmental reporting in Malaysia compared to its predecessor segmental reporting under IAS14. Based on the Annual Reports of top 53 by market capitalization companies listed on the main board of Bursa Malaysia in 2003, findings indicate that MASB 22 has improved segment disclosure practices of sample companies compared to IAS 14 regime, with greater number of line of business and geographical segments reported by sample companies.